Natural Bacterial Assemblages in Arabidopsis thaliana Tissues Become More Distinguishable and Diverse during Host Development - Kathleen Beilsmith (American Society for Microbiology, 2021)
Developing synthetic microbial communities that can increase plant yield or deter pathogens requires basic research on several fronts, including the efficiency with which microbes colonize plant tissues, how plant genes shape the microbiome, and the microbe-microbe interactions involved in community assembly. Findings on each of these fronts depend upon the spatial and temporal scales at which plant microbiomes are surveyed.